Ileal Pouch Excision can Be Performed With Similar Outcomes in Obese Patients Compared to Nonobese Counterparts: An Assessment From American College of Surgeons National Surgical Quality Improvement Program. Issue 12 (December 2022) - Esen, Eren; Aytac, Erman; Aydinli, H. Hande; Grieco, Michael J.; Erkan, Arman; Kirat, Hasan T.; Schwartzberg, David M.; Baca, Bilgi; Karahasanoglu, Tayfun; Remzi, Feza H.
Background: Failed pouches may tend to be managed with only a loop ileostomy in obese patients due to some safety concerns. The effect of obesity on ileal pouch excision outcomes is poorly studied. In our study, we aimed to assess the short-term outcomes after ileal pouch excision in obese patients compared to their nonobese counterparts. Methods: The patients who underwent pouch excision between 2005 and 2017 were included using ACS-NSQIP participant user files. The operative outcomes were compared between obese (BMI ≥30 kg/m 2 ) and nonobese (BMI<30 kg/m 2 ) groups. Results: There were 507 pouch excision patients included of which eighty (15.7%) of them were obese. Physical status of the obese patients tended to be worse (ASA>3, 56.3 vs 42.9%, P = .027). There were more patients who had diabetes mellitus (DM) and hypertension (HT) in the obese group (26.3% vs. 11.2%, P = .015; 11.3 vs. 4.4%, P < .001, respectively). Operative time was similar between 2 groups (mean ± SD, 275 ± 111 vs. 252±111 minutes, P = .084). Deep incisional SSI was more commonly observed in the obese group (7.5 vs 2.8%, P = .038). In multivariate analysis, only deep incisional SSI was found to be independently associated with obesity (OR: 2.79, 95% CI: 1.02-7.67). Obese patients were readmitted more frequently than nonobese counterparts (28.3 vs 16%, P = .035). The length of hospital stay was comparable [median (IQR), 7 (4-13.5) vs. 7 (5-11) days, P = .942]. Conclusion: Ileal pouch excision can be performed in obese patients with largely similar outcomes compared to their nonobese counterparts although obesity is associated with a higher rate of deep space infection.